Silica‐carrying particulate matter enhances Bjerkandera adusta‐induced murine lung eosinophilia. Issue 1 (21st July 2014) - He, Miao; Ichinose, Takamichi; Liu, Boying; Song, Yuan; Yoshida, Yasuhiro; Kobayashi, Fumihisa; Maki, Teruya; Yoshida, Seiichi; Nishikawa, Masataka; Takano, Hirohisa; Sun, Guifan
ABSTRACT: Bjerkandera adusta ( B. adusta ) causes fungus‐associated chronic cough. However, the inflammatory response is not yet fully understood. Recently, B. adusta was identified in Asian sand dust (ASD) aerosol. This study investigated the enhancing effects of ASD on B. adusta ‐induced lung inflammation. B. adusta was inactivated by formalin. ASD was heated to remove toxic organic substances. ICR mice were intratracheally instilled with saline, B. adusta 0.2 µg, or B. adusta 0.8 µg with or without heated ASD 0.1 mg (H‐ASD), four times at 2‐week intervals. Two in vitro experiments were conducted to investigate any enhancing effects using bone marrow‐derived macrophages (BMDM) from Toll‐like receptor (TLR) knockout mice and ICR mice. Co‐exposure to H‐ASD and B. adusta, especially at high doses, caused eosinophil infiltration, proliferation of goblet cells in the airway, and fibrous thickening of the subepithelial layer, and remarkable increases in expression of Th2 cytokines and eosinophil‐related cytokine and chemokine expression in bronchoalveolar lavage fluid. In the in vitro study using BMDM from wild‐type, TLR2−/−, and TLR4−/− mice, the TLR‐signaling pathway for cytokine production caused by B. adusta was predominantly TLR2 rather than TLR4. H‐ASD increased the expression of NF‐κB and cytokine production by B. adusta in BMDM from ICR mice. The results suggest that co‐exposure to H‐ASD and B. adusta caused aggravated lung eosinophilia via remarkable increases of pro‐inflammatory mediators. The aggravation of inflammation may be related, at least in part, to the activation of the TLR2–NF‐κB signaling pathway in antigen presenting cells by H‐ASD. © 2014 Wiley Periodicals, Inc. Environ Toxicol 31: 93–105, 2016.